Anthropometry based prediction of dominant hand grip strength in Indian office going females - Rawat, S; Varte, L R; Singh, I J; Choudhary, S; Singh, S (Asian Journal of Medical Sciences, 2016)
Background: Physical strength can be measured by means of hand grip strength. It is of great use as a functional index of nutritional status. Aims and Objectives: Physical strength can be measured by means of hand grip strength. It is of great use as a functional index of nutritional status. Association of hand grip strength with other variables is studied in order to predict the strength outcomes and to study the effect of factors that can influence hand grip strength performance. Materials and Methods: In the present study the correlations of dominant hand grip strength and anthropometric and body composition variables namely, height, weight, forearm length, arm length, hand breadth, body mass index (BMI), and fat mass in randomly selected 375 unrelated, normal, healthy Indian office going females of age 20-60 years with mean height and weight of 154.12 ± 5.94 cm and 59.86 ± 10.94 kg respectively has been studied. Result: Hand grip strength of the females varied from 17 kg to 32 kg with a mean of 23.86 ± 2.74 kg. The comparison of age, height, weight, forearm length, arm length, hand breadth, and fat mass with the hand grip strength showed good correlation (p<0.01). The best fit model for handgrip prediction when age, height, weight and hand breadth for this population were considered is Hand Grip = -12.260-0.13*Age+0.16*Height+0.13*Weight+1.02*Hand breadth. Conclusion: It may be concluded that hand grip strength has close association with the anthropometric measurements and body composition variables and using these parameters grip strength can be predicted in Indian office going females. Asian Journal of Medical Sciences Vol.7(5) 2016 58-62